Cytochrome P450 Enzymes in Pharmacology: Regulation, Variability, and Drug Interaction Mechanisms - Al-Hassani, Zahraa K.; Ghani, Zahraa Nasser Abdul; Abbood, Mohammed Khalid (Journal of Science in Medicine and Life, 2025)
The cytochrome P450 enzyme (CYP450) family consists of a diverse superfamily of heme-thiolate monooxygenases in the metabolism of many endogenous and xenobiotic compounds. The enzymes influence the kinetics, dynamics and therapeutic efficacy of drugs. They are under strong genetic, environmental and physiological regulation with significant interindividual variation in drug response. Polymorphisms of genes encoding CYP450 enzymes, in particular CYP2D6, CYP2C19 and CYP3A4, are clinically relevant and have been related to differences in the metabolism of Desipramine (DMI) as well as its adverse drug reactions (ADRs). Furthermore, drug–drug interactions can also induce or inhibit expression of CYP enzymes after coadministration of other drugs and dietary constituents with induction/reduction followed by dose adjustment or therapeutic drug monitoring being important in clinical medicine. This review provides a comprehensive analysis of the regulation and versatility of the CYP450 and their participation in clinically relevant drug-drug interactions (DDIs). The focus is on the latest discoveries that advance our knowledge in the CYP-related pharmacokinetic variability and support precision pharmacotherapy approach.